2006
DOI: 10.1038/sj.ki.5000306
|View full text |Cite
|
Sign up to set email alerts
|

Increase of circulating neutrophil and platelet microparticles during acute vasculitis and hemodialysis

Abstract: Release of microparticles (MPs) from blood cells may occur upon various activation signals. MPs from neutrophil and platelet have been studied in systemic infectious diseases and cardiovascular diseases, respectively. They are here investigated in common nephropathies including vasculitis and dialysis, two conditions characterized by neutrophil activation. Flow cytometry analysis of neutrophil-derived (CD66b-positive) and platelet-derived (CD41a-positive) MPs was performed on 213 plasma samples from patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
125
2
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(137 citation statements)
references
References 51 publications
6
125
2
4
Order By: Relevance
“…A previous study demonstrated that, even in patients with severe CKD (end-stage renal disease on hemodialysis), the circulating MP levels were significantly increased only in the presence of reduced whole blood viscosity and shearing stress 42) . Other authors have documented elevated levels of MPs due to acute vascular damage, rather than chronic vasculitis, resulting from renal disease 43) . In the present study, all patients with CKD-AP had chronic kidney vascular disease associated with CKD.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study demonstrated that, even in patients with severe CKD (end-stage renal disease on hemodialysis), the circulating MP levels were significantly increased only in the presence of reduced whole blood viscosity and shearing stress 42) . Other authors have documented elevated levels of MPs due to acute vascular damage, rather than chronic vasculitis, resulting from renal disease 43) . In the present study, all patients with CKD-AP had chronic kidney vascular disease associated with CKD.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…These particles circulate in the blood and have the ability to mediate both inflammation and thrombosis [25][26][27][28][29][30] . Increased numbers of circulating MPs have been reported in a wide range of diseases 25) , including acute coronary syndrome 31) , infectious diseases 32) , diabetes mellitus 33) , uremia 34) and hematologic 35,36) and other malignancies 37,38) . However, it is not currently known whether MPs may be used as biomarkers for predicting the presence of CRS and/or cardiorenal disease (CRD).…”
Section: Blood Sampling For Biochemistry Blood Cell Count Study and mentioning
confidence: 99%
“…Circulating MPs have been the most studied EVs in humans with CKD and ESRD, conditions in which MPs have been associated with endothelial dysfunction, 67 cardiovascular mortality, 68,69 increased risk for calcification, 70,71 anemia, 72,73 and disease-specific alteration in coagulation. 74 In a study of a heterogeneous group of patients with chronic renal failure and those on peritoneal dialysis and hemodialysis, all patients compared with healthy controls had higher levels of endothelial-derived microparticles (EMPs) and MPs of leukocyte origin.…”
Section: Ckd/uremia/esrdmentioning
confidence: 99%
“…Most of the data on PMN-derived EVs (called in these studies ectosomes) come from the laboratory of Dr. Schifferli [26,[34][35][36]39,40,45,[93][94][95][96]. They characterized the size and surface properties of EVs released upon fMLP-stimulation and came to the conclusion that both the in vitro and the in vivo generated EVs are right-side out [39,45].…”
Section: Role Of Pmn-derived Vesicles In Communicationmentioning
confidence: 99%